2011
DOI: 10.1016/j.ijfoodmicro.2010.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of yogurt starter cultures on the survival of Lactobacillus acidophilus

Abstract: Recognized to confer health benefits to consumers, probiotics such as Lactobacillus acidophilus are commonly incorporated into fermented dairy products worldwide; among which yogurt is a popular delivery vehicle. To materialize most of the putative health benefits associated with probiotics, an adequate amount of viable cells must be delivered at the time of consumption. However, the loss in their viabilities during refrigerated storage has been demonstrated previously. This study focused on the effects of yog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
72
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 37 publications
1
72
0
3
Order By: Relevance
“…Gee et al (2007) reported that addition of highly concentrated barley beta-glucan had no significant effect on the ability of the starter cultures to ferment. Low pH (4.6) and glucono delta lacton accumulation had no effect on the survival of L. acidophilus strains (Ng, 2011). As a similar result, Farnworth et al (2007) reported that the falls of the pH values were faster in the soybeverage than in milk.…”
Section: Changes Of Chemical Compositions Of Yogurt During Fermentationmentioning
confidence: 67%
See 2 more Smart Citations
“…Gee et al (2007) reported that addition of highly concentrated barley beta-glucan had no significant effect on the ability of the starter cultures to ferment. Low pH (4.6) and glucono delta lacton accumulation had no effect on the survival of L. acidophilus strains (Ng, 2011). As a similar result, Farnworth et al (2007) reported that the falls of the pH values were faster in the soybeverage than in milk.…”
Section: Changes Of Chemical Compositions Of Yogurt During Fermentationmentioning
confidence: 67%
“…Donkor et al (2006) concluded that the decrease in L. acidophilus cell numbers in yogurts was the result of lactic acid and acetic acids accumulation. Moreover, Ng et al (2011) reported that the level of organic acids was found to have a more pronounced effect on the strain's variability than the pH value. Sahan et al (2008) reported that use of β-glucan hydrocollidal composite in the manufacture of non-fat yogurt did not significantly influence pH, titratable acidity, acetaldehyde, volatile fatty acid and tyrosine contents at any storage time.…”
Section: Changes Of Chemical Compositions Of Yogurt During Fermentationmentioning
confidence: 99%
See 1 more Smart Citation
“…bulgaricus (Lb); samples prepared with these starter bacteria are labeled Lb-St [1]. In the early stage of the incubation process, Lb stimulates the growth of St releasing amino acids from casein (where the most important is valine) and producing a moderate reduction in pH due essentially to St [2,3]; furthermore, from the start of the process, new chemical structures (exopolysaccharides (EPS) and organic phosphate) are produced.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that during the course of Lactobacillus mediated fermentations, organic acids were released, proteins hydrolyzed and anti-oxidant ferulic acid from plant cell wall materials solubilized (Cheigh et al, 1994). It has been reported that fermentation of Anoectochilus formosanus using Lactobacillus acidophilus boosted its anti-oxidant activity by increasing the total phenol content (Ng et al, 2011). In another study, fermentation was used to enhance the antimicrobial potential of the crude herbal extract of Phyllanthus niruri.…”
Section: Introductionmentioning
confidence: 99%